Complexation Study of 18-Crown-6 with Alkali Metal Ions in Ethanol + Water Binary Mixtures by Conductometric Technique and Assessment of Thermodynamic Parameters - Hossen, Md. Delwar; Islam, Md. Minhajul; Ahmed, Md. Jobayer; Kabir, Md. Alamgir; Khan, Md. Nuruzzaman; Roy, Pijush Kanti (Asian Journal of Chemistry, 2026)
A conductometric investigation of the complexation of two alkali metal ions with 18-crown-6 has been performed in binary ethanol + water solvent mixtures at four different temperatures viz. 303.15 K, 308.15 K, 313.15 K and 318.15 K. The conductance analysis revealed that 18-crown-6 forms 1:1 complexes with alkali metal ions. The molar conductance of K+ ion was higher than Na+ ion but the stability constant followed the reverse order. For every case, the stability constant decreases with increasing temperature. The stability constants for the CE-Na+ complexes followed the sequence 80% > 60% > 40% > 20% v/v at 303.15 K, while those for the CE-K+ complexes were 80% > 40% > 60% > 20% v/v at the same temperature. Thermodynamic parameters revealed that the values of Gibb’s free energy, enthalpy and entropy were negative, the spontaneity of the complexation process, exothermic in nature and thermodynamically favoured.